TRAINING ON TABLE MANNERS FOR PKK WOMEN, PADANG SAKTI VILLAGE, MUARA ONE DISTRICT, LHOKSEUMAWE CITY - Hamdiah, Hamdiah; Likdanawati, Likdanawati; Putri Mellita Sari, Cut; Thahira Yusral, Syifa; Naja, Safinatun (RADJA PUBLIKA, 2022)
Eating Together is an activity that is often carried out by many people, especially in business cooperation with colleagues or colleagues. The term Table Manner is used as a term for eating ethics and rules in politeness and manners at the dinner table, how to sit, eat, drink using the correct cutlery, and leave the dinner table. The phenomenon found in Padang Sakti village regarding table manners is the lack of understanding of the community regarding the correct procedures for eating and drinking at the dinner table, especially at weddings which are part of official banquets. Where invited guests, especially in-laws, will be served officially. On average, people have very low ethics at banquets (weddings). Low ethics when eating or drinking shows a low social status as well. PKK women who are part of the community are seen as having an important role in shaping the ethics and social status of their community. Therefore, the partners chosen for this community service activity are PKK mothers. The main objective in carrying out table manners training activities for PKK Padang Sakti Village mothers is to develop Human Resources (HR) in the community and increase social status by adding insight, skills and confidence in organizing or attending banquets both within the community itself and outside the community environment. This activity was carried out by 1) Delivering material on banquet procedures, which included room and table arrangements, mealtime sharing, menus, serving rules, how to sit, how to use cutlery, eating procedures, how to talk and emergencies at the dining table. The entire material provided is interspersed with simulations. 2) The training ends with the practice of having a banquet by paying attention to and obeying the general rules of the banquet, including by maintaining ethics during the banquet. Mastery of manners at banquets shows personality and adjustment in relationships. From the training activities carried out, the PKK women in Padang Sakti Village have been able to understand and participate in the training well and understand how to eat good etiquette at the dinner table or commonly referred to as table manner.